Existential threats : American apocalyptic beliefs in the technological era - Vox, Lisa (University of Pennsylvania Press, Inc., 2017)
In Existential Threats, Lisa Vox explores the growth of dispensationalist premillennialism alongside scientific understandings of the end of the world and contends that these two allegedly competing visions have converged to create an American apocalyptic imagination.